Optimization of microwave vacuum drying parameters for germinated lentils based on starch digestibility, antioxidant activity and total phenolic content - Robbarts Nongmaithem; Venkatesh Meda (International Journal of Food Studies)
The aim of this study was to optimize the processing parameters of pulse mode microwave-vacuum drying of germinated green and red lentils (CDC Greenland and CDC Maxim) and investigate the changes in their total phenolic content (TPC), total antioxidant activity (TAA) and In-vitro starch digestibility (SD). The lentils were germinated for 5 days and dried by a pulse mode microwavevacuum method, using 2 s to 8 s out of 10 s pulsed mode at 2000W microwave power and varying the vacuum pressure level between 15 and 45 kPa. In-vitro starch digestibility increased significantly with increased microwave power level. The TPC and TAA appeared to vary distinctively in the two varieties of selected lentils. Vacuum pressure levels did not significantly (p>0.05) affect any responses. Green lentils could be dried at 8 s microwave power and 45 kPa vacuum pressure and red lentils could be dried at 5.5 s microwave power and 42.19 kPa vacuum pressure. The microwave-vacuum drying showed great potential for the drying of germinated lentils.